2014
DOI: 10.14434/v14i4.12823
|View full text |Cite
|
Sign up to set email alerts
|

The effects of implementing recitation activities on success rates in a college calculus course

Abstract: Over a period of six years, three different types of recitation sessions were implemented into the large enrollment section of a college calculus course. During the fall semesters, the results on the departmental final examination, the DFW rates, and the one-year retention rates of students as STEM majors were examined by the type of recitation session used with the large enrollment section. The three types of recitation sessions studied were: (1) optional mentoring sessions at the Math Assistance Center condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is essential, however, that students participate fully in the recitation. Several researchers dealt with students' recitation in face-to-face and online teaching methods (Endorf et al, 2006;Molinari & Mameli, 2013;Staveley-O'Carroll, 2015;Umar & Aziz, 2015;Watt et al, 2014;Wibowo et al, 2018). Wibowo et al (2018) encouraged teachers to consider learning by alternative effort recitation methods of increasing interest and student learning outcomes; increasing students' interest is increasing their attitude towards the subject.…”
Section: Recitationmentioning
confidence: 99%
“…It is essential, however, that students participate fully in the recitation. Several researchers dealt with students' recitation in face-to-face and online teaching methods (Endorf et al, 2006;Molinari & Mameli, 2013;Staveley-O'Carroll, 2015;Umar & Aziz, 2015;Watt et al, 2014;Wibowo et al, 2018). Wibowo et al (2018) encouraged teachers to consider learning by alternative effort recitation methods of increasing interest and student learning outcomes; increasing students' interest is increasing their attitude towards the subject.…”
Section: Recitationmentioning
confidence: 99%
“…Emma insisted that, due to such difficulties, she would not give her students the math problems; rather, she would have them make a 3D example of the surface area calculations to demonstrate the mathematical principles present in the nanotechnology activity. While many studies have demonstrated the importance of using multiple representations in mathematics education, specifically higher mathematics, like calculus (Watt et al, 2014), algebraic representations are essential for mathematics education. The insistence of Emma, and several of her peers, that students, particularly freshman, benefit from visual aids is not contested, yet the avoidance of numeric and algebraic representations could certainly leave a student body ill-prepared for higher mathematics.…”
Section: Teacher Learning Shaped By Past Teaching and Learning Experimentioning
confidence: 99%